Media stickiness and cognitive imprinting: inertia and creativity in cooperative work & learning with ICTs - Geer, Ruth (2006)
This paper attempts to build a bridge between the fields of Computer Supported Cooperative Work and learning in online communities. Of particular importance is their use of information and communication technologies. Each field has independently developed notions of inertia in the behaviour of users of these technologies. The notion of media stickiness is examined and related to that of imprinting in learning communities. Various suggestions are made of value to both fields and further research identified.